2019
DOI: 10.3390/w12010135
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Soil Erosion and Sediment Yield in the Lancang–Mekong River Using the Modified Revised Universal Soil Loss Equation and GIS Techniques

Abstract: The Lancang–Mekong River basin, as an important transboundary river in Southeast Asia, is challenged by rapid socio-economic development, especially the construction of hydropower dams. Furthermore, substantial factors, such as terrain, rainfall, soil properties and agricultural activity, affect and are highly susceptible to soil erosion and sediment yield. This study aimed to estimate average annual soil erosion in terms of spatial distribution and sediment deposition by using the revised universal soil loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 62 publications
0
49
0
2
Order By: Relevance
“…For this study, observed soil sediment data from field surveying was not performed. However, the observed soil sediment data and the sediment yield results from RUSLE model simulation were well correlated with a correlation higher than 0.9 (Chuenchum et al, 2020).…”
Section: Soil Loss Estimation With Rusle Modelmentioning
confidence: 82%
See 2 more Smart Citations
“…For this study, observed soil sediment data from field surveying was not performed. However, the observed soil sediment data and the sediment yield results from RUSLE model simulation were well correlated with a correlation higher than 0.9 (Chuenchum et al, 2020).…”
Section: Soil Loss Estimation With Rusle Modelmentioning
confidence: 82%
“…RUSLE model is a very powerful method for estimation of soil erosion in specific situations such as dam construction, mining, typhoon, assessing land management measures, LULC change, and mountain areas (Atoma et al, 2020;Chuenchum et al, 2020;Kassawmar et al, 2018;Kim, 2006;Lazzari et al, 2015;Rammahi and Khassaf, 2018;Somprasong and Chaiwiwatworakul, 2015). RUSLE model integrates remote sensing techniques together with GIS for estimation of the quantity of lost sediment in the four scenarios as shown in Equation (1).…”
Section: Rusle Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, 0.5% to 1% of sedimentation every year influences the capacity limit of reservoirs. The expanded deforestation and destructing man-made exercises everywhere on the world anticipated that by 2050 most of the dams will lose their half of capacity [24]. In Asia, sedimentation has covered approximately 40% of the total storage of reservoirs [25].…”
Section: Of 21mentioning
confidence: 99%
“…Esto último ha condicionado a que se usen con mucha frecuencia las formulaciones empíricas desarrolladas experimentalmente en décadas pasadas que solo permiten calcular la erosión o el aporte de sedimentos (Cohen, Shepherd & Walsh, 2005). A excepción de la ecuación universal de pérdidas del suelo (USLE, por sus siglas en inglés), el resto de las formulaciones no consideran variables y características morfológicas esenciales en los procesos de erosión y transporte de sedimentos de un sistema hidrológico (Chuenchum, Xu & Tang, 2019). Las generalizaciones de estas formulaciones muestran una tendencia hacia la sobreestimación de los procesos (Cohen et al, 2005), por lo cual se deberá tener prudencia en el uso de sus resultados, más aun si se trata del diseño de obras hidráulicas importantes como las presas (Adeogun, Ibitoye, Salami & Ihagh, 2020).…”
Section: Introductionunclassified